Implementation of Inclusive Education Policies in the City of Tangerang Selatan - Nurhayati; Evi Satispi; Izzatusolekha; Rahmat Salam (Global Writing Academica Researching & Publishing, 2023)
Every child has the right to continue to receive education, as mandated by the 1945 Constitution. The inclusive education policy is one of the government’s policies to support the mandate of the 1945 Constitution. Unfortunately, this policy still faces various obstacles, even though it has been implemented since 2009. This research will then be carried out to analyze the process of implementing inclusive education policies in the South Tangerang city area. This research is descriptive qualitative research. The data used in this study were obtained through interviews, observation and document studies. The results of this study then found that implementing inclusive education policies in Tangerang is still not going well completely. This is because there is still no specific legal basis regarding inclusive education, the budget is still dependent on the provincial government, and there is no SOP for implementing inclusive education. Therefore, the government needs to clarify the legal umbrella or legal basis for inclusive education to clarify the SOPs, budget and maximum implementation.